Z badań nad językiem piśmiennictwa nowogródzkiego z okresu międzywojennego. Elementy północnokresowe w języku Józefa Żmigrodzkiego - Lewaszkiewicz, Tadeusz (Forum Lingwistyczne, 2019)
The Nowogródek i okolice [Nowogródek and environs] tourist guide by Józef Żmigrodzki occasionally reveals some phonetic features typical for North-Eastern Borderlands Polish (rznięty, najprzód, szkarpa), peculiar noun inflections (uczni, soft instead of hard adjectival stem – bezleśni), peculiar adjectival and adverbial gradation forms (najpamiętniejszy, najkonieczniejszy, szczególniej), emphasising word using the -ż particle (temuż). Typical word formation features include the adverbial suffix -o instead of -’e (zaledwo) and 23 peculiar prefixed verbs (e.g. pobudować – zbudować ). Syntax features present in the work include a total of 6 language structures: adjective/participle predicate in the locative instead of nominative case (2), historic non-compound form of the passive participle in the predicate (1), verbs governing unusual cases (3). Word material is much more abundant, with 63 single lexical units, 6 peculiar phrases and 1 peculiar expression. The text of Żmigrodzki’s book undoubtedly bears witness to the North-Eastern Borderlands heritage of its author. Other interwar writings originating from the North-Eastern Borderlands should be the subject of linguistic studies as well.